Edukasi Perkembangan Financial Technology Sebagai Upaya Pencegahan Perilaku Konsumtif Masyarakat Dari Pinjaman Online - Paroli, Paroli; Rusdian, Suca (Society : Jurnal Pengabdian Masyarakat, 2024)
The growth of fintech, especially the P2P lending model, has simplified the procedure of borrowing money and made it faster and easier. The main advantage of online loans, especially through fintech platforms, is their ease of use. The existence of online lending fintech brings positive impacts as well as negative risks for society. Some aspects that need to be considered regarding this negative impact include, Consumer Misunderstanding, Material and Non-Material Losses, Privacy Concerns, Unethical Billing. The aim of this activity is to educate the public to understand financial technology (fintech), one of which is online loans in an effort to prevent consumer behavior. This educational method is a community gathering activity, where the people present are given an understanding of the development of financial technology and online loans.